Dimensional Effects in Micro- and Nanostructural Changes in Grain and Intragrained Structure of Steel 45 at Static-pulse Treatment - A.V. Kirichek; A.P. Kuzmenko; D.L. Soloviev; S.V. Barinov; A.Yu. Altukhov; S.A. Silantiev; A.N. Grechukhin; Myo Min Than; M.B. Dobromyslov (Журнал нано- та електронної фізики)
Conducted macro-, micro- and nanostructured materials were investigated by the influence of sample sizes of steel 45 in the form of a parallelepiped, after intense static pulse processing in plastic deformation as in the single (150 J), and pulsed (25 J) impact with a frequency of 23 Hz. When all modes of processing bulk samples found structuring self-organized formation of dislocations. With a single exposure revealed as filling pearlite grains periodic dislocations (200 nm), and the formation of dislocation-free regions. When a periodic pulse treatment of the samples with transverse dimensions fold speed of propagation of elastic waves and shock waves as well as the related transport velocity of dislocations turns shockwave mechanism causing the formation of alternating strips of ferritic and pearlite walls (25 microns), wherein the pearlite wall completely or partially filled with dislocations.